2019
DOI: 10.1029/2019gl085833
|View full text |Cite
|
Sign up to set email alerts
|

First SWARM Observations of the Artificial Ionospheric Plasma Disturbances and Field‐Aligned Currents Induced by the SURA Power HF Heating

Abstract: A series of experiments were conducted with a conjunction between the midlatitude SURA ionospheric heating facility and the multisatellite SWARM mission. We present the first observations made by SWARM on the plasma perturbations and electric currents induced in the F2 region ionosphere by the high‐power high‐frequency O‐mode radio wave pumping. In the heated region, significant effects include a localized increase of the electron temperature accompanied by stratification of the electron density and the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…The lower altitudes, 400–500 km, are of particular interest because they conform to the transition from the region where the generation of the most intensive plasma heating takes place and the most intensive artificial ionospheric turbulence are observed, to the region where the HF‐disturbed plasma spreads from the ionosphere F2 region to the outer ionosphere and magnetosphere. No observational data on the properties of plasma turbulence induced by the high‐power HF pumping at this altitudinal range existed except for the recent first results obtained during joint experiments using Swarm (Frolov et al., 2018; Lukianova et al., 2019).…”
Section: Results Of the Joint Sura‐norsat‐1 Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower altitudes, 400–500 km, are of particular interest because they conform to the transition from the region where the generation of the most intensive plasma heating takes place and the most intensive artificial ionospheric turbulence are observed, to the region where the HF‐disturbed plasma spreads from the ionosphere F2 region to the outer ionosphere and magnetosphere. No observational data on the properties of plasma turbulence induced by the high‐power HF pumping at this altitudinal range existed except for the recent first results obtained during joint experiments using Swarm (Frolov et al., 2018; Lukianova et al., 2019).…”
Section: Results Of the Joint Sura‐norsat‐1 Experimentsmentioning
confidence: 99%
“…Besides, DMSP satellites observed ducts over HAARP and SURA with ion outflow (Frolov et al., 2008; Milikh et al., 2010; Vartanyan et al., 2012). Recently, a study that described the first Swarm observations of artificial ionospheric plasma disturbances and field‐aligned currents induced by HF heating from the SURA facility (Frolov et al., 2018; Lukianova et al., 2019) was published. Furthermore, using CSES satellite data, it was shown that the power spectrum density of the electric field was larger by an order of magnitude in the region heated by the SURA facility as compared with the background (Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dayside plasmapause correlated with the delayed time history of the small-scale FAC boundary and this behaviour was interpreted as a direct consequence of co-rotation with the plasmapause, formed on the night side, propagating to the dayside by rotating with the Earth. Swarm satellite observations were used to characterize the extreme behaviour of large-and small-scale FACs during the severe magnetic storm of September 2017 (Lukianova 2020). The dawn-dusk asymmetry was observed as enhanced dusk-side region 2 FACs in both hemispheres.…”
Section: Solar Solar Wind and Magnetospheric Drivers Of Variabilitymentioning
confidence: 99%
“…The observation of particles and waves causing space storms with a single satellite inherently suffers from space-time ambiguity. Recently, such ambiguity has often been resolved using multi-satellite observations such as those on the CLUSTER [120], THEMIS [121], MMS [122], and SWARM [123] missions; however, the inter-satellite distances of these satellites were generally vast (> 100 km). Hence, small-scale plasma phenomena on low altitude orbit have not been studied well.…”
Section: Snipementioning
confidence: 99%